MAPPING THE PROMOTION OF COMMERCIAL SEX SERVICES USING THE MICHAT APPLICATION: FROM PREVENTION TO SOLUTIONS - Christiany Juditha (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2022)
The disclosure of several cases of online prostitution using the MiChat application in major cities of Indonesia shows that the phenomenon of prostitution is increasing. Prostitution practices are prohibited in Indonesia as it included in human trafficking. Furthermore, prostitution using virtual networks is part of cyber-crime regulated in the Electronic Information and Transactions Law. Despite the existing regulations, online prostitution activity continues. One of the reasons is the use of social media and online applications that facilitate the distribution of sexual services. This study aims to obtain an overview of online prostitution activity through the MiChat application and its solutions. This study used a content analysis method equipped with interviews with informants who are competent in handling prostitution. The results of the study concluded that the 'people nearby' feature in the MiChat application was dominated by accounts aimed at online prostitution, including the promotion of sexual services through profile information, timelines, and uploading photos/ videos related to service offerings, payment execution, also customer testimonials. Various efforts have been made by the government by blocking negative content regarding prostitution, but unfortunately, the platform itself has not been closed. In addition, all parties have taken preventive measures in terms of the prevention and handling of online prostitution.